A Review: The Manifestations, Mechanisms, and Treatments of Musculoskeletal Pain in Patients With COVID-19 - Wang, Lijuan; Yang, Na; Yang, Jinfeng; Zhao, Shuwu; Su, Chen (Frontiers in Pain Research, 2022)
The outbreak of COVID-19 poses a serious threat to global health. Musculoskeletal (MSK) pain is the most frequent symptom in patients with COVID-19 besides fever and cough. There are limited studies addressing MSK symptoms in patients with COVID-19. This review aims to provide an overview of current studies related to MSK pain in patients with COVID-19, summarize the possible mechanisms of myalgia, and describe the current management options. In addition to acute respiratory manifestations, COVID-19 might also affect neurological systems which include skeletal manifestations and muscular injury. A possible mechanism of MSK pain and myalgia in COVID-19 may be related to the distribution of angiotensin-converting enzyme 2 (ACE-2) and the occurrence of cytokine storms. ACE-2 has been shown to be the receptor of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2). Moreover, studies have shown that inflammatory cytokines could cause myalgia by inducing prostaglandin E2 (PGE2) production. In addition, it was also found that the plasma levels of IL2, IL7, IL10, IL-6, TNFα, and e lymphopenia were higher in patients with COVID-19. In general, the treatment of MSK pain in patients with COVID-19 falls into pharmacological and non-pharmacological interventions. Various treatments of each have its own merits. The role of vaccination is irreplaceable in the efforts to prevent COVID-19 and mitigates its subsequent symptoms.